2013
DOI: 10.1088/1751-8113/46/25/254019
|View full text |Cite
|
Sign up to set email alerts
|

Finite size Lyapunov exponent: review on applications

Abstract: In dynamical systems, the growth of infinitesimal perturbations is well characterized by the Lyapunov exponents. In many situations of interest, however, important phenomena involve finite amplitude perturbations, which are ruled by nonlinear dynamics out of tangent space, and thus cannot be captured by the standard Lyapunov exponents. We review the application of the finite size Lyapunov exponent (FSLE) for the characterization of noninfinitesimal perturbations in a variety of systems. In particular, we illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 114 publications
8
63
0
Order By: Relevance
“…Here, we follow the excellent review [Cencini and Vulpiani(2013)], where applications to L96 were also discussed. Given a generic trajectory x(t), the idea is to define a series of thresholds δ n = δ 0 σ n , with σ > 1, and to measure the times τ (δ n ) needed by the norm of a finite perturbation ∆x(t) = x (t) − x(t) to grow from the amplitude δ n to δ n+1 .…”
Section: Finite Perturbationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we follow the excellent review [Cencini and Vulpiani(2013)], where applications to L96 were also discussed. Given a generic trajectory x(t), the idea is to define a series of thresholds δ n = δ 0 σ n , with σ > 1, and to measure the times τ (δ n ) needed by the norm of a finite perturbation ∆x(t) = x (t) − x(t) to grow from the amplitude δ n to δ n+1 .…”
Section: Finite Perturbationsmentioning
confidence: 99%
“…(28). The FSLE in principle depends on the norm used to define the size of the perturbation [Cencini and Vulpiani(2013)]. However, by construction, for vanishing perturbations, the FSLE should coincide with the largest LE regardless of the norm lim δ→0 Λ(δ) = λ 1 .…”
Section: Finite Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of the divergence of two trajectories separated by a finite distance δ x (x) is not necessarily well described by exp(−λ t (x)t) (see Ref. [18] for more on finite-size Lyapunov exponents). This violation is more evident in trajectories x where λ t (x) < 0.…”
Section: A Logistic Mapmentioning
confidence: 99%
“…This has given rise to the notion of scale dependent error growth: the conventional Lyapunov exponent should be replaced by a scale dependent quantity, e.g. a finite size Lyapunov exponent [12]. Indeed, in a study of scale dependent error growth in the Global Forecast System of the National Center for Environmental Prediction, Harlim et al [13] have shown that there is a scale dependent error growth rate which becomes very large if the errors become small (see figure 1 in [13]).…”
Section: Introductionmentioning
confidence: 99%